Invasive and non-invasive techniques for detecting portal hypertension and predicting variceal bleeding in cirrhosis: A review. (February 2014) - Zardi, Enrico Maria; Di Matteo, Francesco Maria; Pacella, Claudio Maurizio; Sanyal, Arun J.
Abstract Portal hypertension is a severe syndrome that may derive from pre-sinusoidal, sinusoidal, and post-sinusoidal causes. As a consequence, several complications (i.e. ascites, oesophageal varices) may develop. In sinusoidal portal hypertension, hepatic venous pressure gradient (HVPG) is a reliable method for defining the grade of portal pressure, establishing the effectiveness of the treatment, and predicting the occurrence of complications; however, some questions exist regarding its ability to discriminate bleeding from non-bleeding varices in cirrhotic patients. Other imaging techniques (transient elastography, endoscopy, endosonography, and duplex Doppler sonography) for assessing causes and complications of portal hypertensive syndrome are available and may be valuable for the management of these patients. In this review, we evaluate invasive and non-invasive techniques currently employed to obtain a clinical prediction of deadly complications, such as variceal bleeding in patients affected by sinusoidal portal hypertension, in order to create a diagnostic algorithm to manage them. Again, HVPG appears to be the reference standard to evaluate portal hypertension and monitor the response to treatment, but its ability to predict several complications and support management decisions might be further improved through the diagnostic combination with other imaging techniques.